Effect of different concentrations of fluoride in dentifrices on dentin erosion subjected or not to abrasion in situ/ex vivo - Magalhaes, A. C. [UNESP]; Rios, D.; Moino, A. L.; Wiegand, A.; Attin, T.; Buzalaf, M. A. R. (Karger, 2008)
This in situ/ex vivo study assessed the effect of different concentrations of fluoride in dentifrices on dentin subjected to erosion or to erosion plus abrasion. Ten volunteers took part in this crossover and double-blind study performed in 3 phases (7 days). They wore acrylic palatal appliances containing 4 bovine dentin blocks divided in two rows: erosion and erosion plus abrasion. The blocks were subjected to erosion by immersion ex vivo in a cola drink (60 s, pH 2.6) 4 times daily. During this step, the volunteers brushed their teeth with one of three dentifrices D (5,000 ppm F, NaF, silica); C (1,100 ppm F, NaF, silica) and placebo (22 ppm F, silica). Then, the respective dentifrice slurry (1: 3) was dripped on dentin surfaces. While no further treatment was performed in one row, the other row was brushed using an electric toothbrush for 30 s ex vivo. The appliances were replaced in the mouth and the volunteers rinsed with water. Dentin loss was determined by profilometry and analyzed by 2-way ANOVA/Bonferroni test (alpha = 0.05). Dentin loss after erosive-abrasive wear was significantly greater than after erosion alone. Wear was significantly higher for the placebo than for the D and C dentifrices, which were not significantly different from each other. It can be concluded that the presence of fluoride concentrations around 1,100 ppm in dentifrices is important to reduce dentin wear by erosion and erosion + abrasion, but the protective effect does not increase with fluoride concentration. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: erosion; fluoride; soft drinks; toothbrushing abrasion